Structural aspects and vein systems relations of the Segovia-Remedios mining district - Echeverry-Castañeda, Sebastián; Cárdenas-Vera, Alán Fernando; Ordóñez-Carmona, Oswaldo; Muñoz-Aguirre, Oscar (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
Gold mineralizations northeast Antioquia are located in the eastern flank of the Otú-Pericos Fault System, within Segovia Batholith. Vein systems in the district have been characterized and organized in three ain systems: Silencio, Vertical y Cogote.  Relationships of several structural aspects among these systems, as well as identification of structures not reported previously and believed not present aloud to sketch and approximate to history and evolution of the mining district and therefore the implications of these structural controls to the present mineralizations.  The presence of older dykes than veins which indorse some of the most important veins in the region and the fact that veins are younger that fracture generation as they cross the system, suggest that all processes could be the result of regional adjustment in the collision processes between terrains limited by Otú-Pericos fault System.